Analysis of mass transfer and morphometric characteristics of white mushroom (Agaricus bisporus) pilei during osmotic dehydration. (January 2019) - González-Pérez, J.E.; López-Méndez, E.M.; Luna-Guevara, J.J.; Ruiz-Espinosa, H.; Ochoa-Velasco, C.E.; Ruiz-López, I.I.
Abstract: The shrinkage-deformation (SD) behavior and mass transfer characteristics of white mushroom ( Agaricus bisporus ) pilei during osmotic dehydration (OD) were investigated. The morphometric characteristics of the product (including product contours, cross-sectional area and roundness) were obtained from digital images. Moreover, product contours were averaged to extract relevant deformation characteristics of osmodehydrated samples. An unsteady state 2D-diffusion model taking into account both radial and angular mass transfer, where product is shaped as a hemispherical shell was proposed to describe experimental data. Water and solute diffusivities in product were estimated with and without considering product shrinkage, defined as the shortening of radial dimension. Besides, diffusion coefficients were obtained using simplified models for both the proposed hemispherical shell geometry and a simpler sphere-shaped product, in the latter, under different similitude criteria. Estimated water and solute diffusivities reflecting dimensional changes of product were in the ranges of 1.1–4.6 × 10 −10 and 1.5–1.8 × 10 −10 m 2 /s, respectively, and are overestimated in about 39–113% for water and in about 24–66% for solute when shrinkage is not included in the OD model. Moreover, diffusion coefficients can also be corrected for geometry using the appropriate similitude criterion. Highlights: Morphometric changes of white mushroom pilei during OD were evaluated. Real product shape was approximated by a hemispherical shell geometry. A 2D unsteady-state diffusion model was proposed to describe mass transfer. Product suffers a significant shrinkage and deformation during OD. Shrinkage is of key importance for an accurate estimation of diffusivities.